Geometric Redesign of the Access Road to Turyapada Tower Mountain Tourism in Bali - Muhammad Zainul Arifin; Muh Miftahulkhair; Ellyni Dwi Fortuna; Siti Blatiskha Rahmadella Yuga; Hendi Bowoputro; Muhammad Abdy (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
Mountain tourism access roads require geometric designs that accommodate terrain constraints, design vehicles, operational safety, and applicable standards. This study evaluates and redesigns the access road to Turyapada Tower Technology Park, Bali, from STA 0+000.00 to STA 1+851.84. Project topographic data, planning documents, and alignment worksheets were analyzed and harmonized with the 2021 Indonesian Road Geometric Design Guidelines. Horizontal and vertical alignments, terrain classification, design speed, curve configuration, longitudinal grade, and earthwork volumes were evaluated using AutoCAD Civil 3D and SketchUp. The final design adopts a 20 km/h design speed and a two-lane two-way undivided configuration. Segment I uses 3.5 m lanes and four spiral-spiral curves, Segment II uses 3.0 m lanes and sixteen spiral-spiral curves, while Segment III uses 3.0 m lanes and nine operational full-circle curves. The maximum longitudinal grade was reduced from 17.11% to 14.98%. Earthwork analysis indicates net excavation in Segments I and II and net embankment in Segment III. The findings demonstrate that mountain tourism access roads require integrated consideration of geometric standards, digital modelling, terrain characteristics, and low-speed operational safety.